Technique for wireless reading of passive microfluidic sensors. Issue 3 (1st February 2018) - Henry, D.; Aubert, H.; Pons, P.; Lorenzo, J.; Lázaro, A.; Girbau, D.
Abstract : The remote reading of high‐resolution microfluidic and passive (i.e. batteryless and chipless) temperature sensors is focused. These sensors are remotely interrogated from a 24 GHz frequency‐modulated continuous‐wave radar performing a mechanical beam scanning for locating the sensors and measuring the variation of sensors electromagnetic echo level due to temperature fluctuation. From radar measurement data, an estimator is proposed here for determining the meniscus position of the fluid inside the sensors microchannel and for deriving the temperature at the sensors location. It is shown that the estimator presents a convenient linear dependence with the meniscus position at the sensor location. The smallest measurable variation of the meniscus position is of 40 µm.